La literatura perduda de Joan Roís de Corella: les fonts - Martos, Josep Lluís (Caplletra. Revista Internacional de Filologia, 2008)
The lost literature of an author provides data that, in spite of being partial, are important to better understand his preserved work and the complexity of his literary work. This article offers an approach to the losses experienced by Joan Roís de Corella’s literature down the centuries, in the full meaning of the term. It focuses on the analysis of the sources that supply information to establish a catalogue of these losses, as a starting point for subsequent work concerning the causes and periods of the disappearances.